Kombinasi Zachman Framework dan Strategic Planning Information System versi John Ward dan Joe Peppard dalam Perancangan Blueprint IT FTI USN Kolaka - Muilyadi; Nurfitria Ningsi; Noorhasanah Zainuddin; Qammaddin (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
This study focuses on designing IT blueprints for the Information Technology Faculty of USN Kolaka by combining the Zachman framework and the Strategic Planning Information System to produce an objective requirements plan. The results of this study suggest that there are at least 11 potential applications, including one strategic application, namely the e-quality assurance application, there are five high priority applications, namely e-monev, e-publication, e-ledger, e-procurement, e-certification, there are also four an application that determines the success of public service operational activities such as e-learning, e-library, e-journal, e-alumni, and then an application that supports public service activities, namely an e-mail application that functions for recording incoming and outgoing letters electronically. Thus, this IT blueprint can be a reference for technology developers in mapping the priorities of FTI USN Kolaka services in the future.